Naringin attenuates liver damage in streptozotocin-induced diabetic rats - Rodriguez, Valeria Andrea (2018)
The aim of this study was to evaluate whether NAR has a hepatoprotective role in a model of STZ-induced diabetes and to elucidate the underlying mechanisms triggered by the flavonoid. Male Wistar rats were divided into three groups: 1) controls, 2) STZ rats 3) STZ rats treated daily with NAR (40 mg/kg b.w.) for 30 days. NAR prevented increases in serum aminotransferases and alkaline phosphatase activities in STZ rats. The flavonoid blocked serum lipid alterations, but not the biometric parameters in STZ rats. Microscopic examination in liver from STZ rats revealed morphological changes indicative of increased adipogenesis and cell death and inflammation, which were all mitigated by the flavonoid. NAR inhibited the NFκB/IL-6/Cox-2 overexpressions triggered by oxidative stress in STZ rats. The iNOS/NO[rad]/nitrosylated protein pathway was also blocked by NAR. The increment in the protein expression of Fas/FasL/caspase-3 and in the Bax/Bcl-2 ratio showed that both pathways of apoptosis were increased by the diabetes, effects that were abrogated by NAR treatment. In conclusion, NAR protects against the liver damage caused by STZ-induced diabetes and it could be a novel therapeutic strategy to prevent the non alcoholic fatty liver disease associated with the type 1Diabetes mellitus.